PUBLIC PERCEPTIONS AND AWARENESS OF CLIMATE CHANGE IN RIVER NILE STATE, SUDAN: BRIDGING KNOWLEDGE GAPS FOR EFFECTIVE ADAPTATION STRATEGIES - Alzepar, Monzer; Omer, Wafa; Abd-Almoniem, Aish; Mergani, Mona; Mohammed, Noura NaserAldeen (International Journal of Research -GRANTHAALAYAH, 2025)
Climate change presents significant global challenges, necessitating a deep understanding of public perception and awareness to inform effective policies and adaptive strategies. This study examines the perceptions, knowledge, and concerns regarding climate change among residents of River Nile State, Sudan, through a cross-sectional survey of 400 respondents. Most participants were female (79%) and had attained university-level education (41.5%), factors likely influencing environmental awareness. Geographic diversity across localities such as Aldamer, Shendi, and Barbar highlights the importance of localized climate impacts and adaptation needs. Participants identified terrorism, infectious diseases, and armed conflict as the most serious threats to human survival, with climate change perceived as less immediate (mean = 3.10). This prioritization of socio-political issues over long-term environmental challenges underscores the need for improved risk communication and public awareness campaigns. While 81% of participants acknowledged rising temperatures over the past decade, only 36% were aware of local environmental policies, revealing a significant gap between climate change awareness and knowledge of policy responses. Participants reported noticeable climate changes, including shifts in rainfall patterns (36%) and temperature (18.8%), consistent with regional climate projections for Africa. Knowledge of specific climate change drivers varied, with greenhouse gases (mean = 4.3) and ocean currents (mean = 4.1) being well understood, while aerosols (mean = 3.2) and deforestation (mean = 3.2) were less familiar, indicating a need for targeted educational initiatives. Air pollution (67.8%) and river pollution (63.5%) were ranked as the most pressing environmental issues, reflecting concerns about immediate health and ecological impacts. Temperature fluctuations (39.8%) and flooding (58.5%) were also considered important. Agriculture, health, and water resources were identified as the sectors most affected by climate change, aligning with global findings on exacerbated food insecurity, water scarcity, and health risks. The study emphasizes the importance of addressing knowledge gaps and integrating climate change into broader environmental and development agendas. Public engagement, participatory approaches, and context-specific adaptation strategies are essential for building climate resilience. By framing climate change within the context of local concerns and enhancing public awareness, this study contributes to the development of inclusive and effective climate adaptation strategies, ultimately supporting sustainable development and environmental sustainability.